Tunisia Urban Development and Local Governance Program : Fiduciary Systems Assessment Report - World Bank (Washington, DC, 2014)
As part of the preparation of the Tunisia Urban and Local Governance Program (ULGP) using the Program for Results (PforR) instrument of the World Bank, the Bank task team carried out a Fiduciary Systems Assessment (FSA) of the Program in accordance with OP/BP 9.0. Based on the findings of the FSA, it is concluded that Program Fiduciary Systems have the capabilities to provide reasonable assurance that the financing proceeds will be used for intended purposes. However considering the existing weaknesses in Program Fiduciary systems, the residual fiduciary risk rating for the Program is rated as Substantial. The Program will finance a portion of the Government of Tunisia s (GoT) existing program for financing municipal service delivery that involves a combination of Capital Grants, and Loans in addition to the Own Source Revenues generated by the municipalities themselves. The PforR Program intends to reform the system of Capital Grants by making it predictable and based on an allocation formula that is principle based and transparent. It has been agreed with client counterparts that GoT will issue a Decree prior to the start of the Program that will spell out the design and operating rules of the reformed capital grant. Indicative allocations for Capital Grants will be included in the Five Year Plans and indicative allocations will be provided by MoEF in advance of the annual plan preparations. The budget allocations for Capital Grants will be transferred from the Treasury Current Account at the Central Bank (BCT) to the Caisse des Prêts et de Soutien des Collectivités Locales (CPSCL) (referred to as the Caisse), who will act as the Program Manager for the ULGP. Caisse will in turn transfer the grant funds to municipalities in accordance with the operating rules for the Unconditional and Conditional Capital Grants. Preliminary assessment of the Program expenditure framework shows that in addition to the changes in the design of the Capital grant through the proposed decree, additional steps such as publishing the indicative allocations of capital grants in advance and reforming the existing system of multiple ex-ante checks and controls into a coordinated system of ex-post controls are necessary for the efficient implementation of the proposed Program.